Enhancing Work Engagement Without Compromising Psychological Well-being: The Role of AI-based EVA in Employee Assistance Program - Hidayah, Nuzulul (Psikologi UHAMKA, 2025)
Abstract Work engagement plays a crucial role in enhancing employee performance and organizational sustainability. While it offers benefits such as increased motivation, productivity, and loyalty, excessive engagement can lead to negative outcomes such as stress, burnout, anxiety, and impaired psychological well-being. To maximize its positive impact while minimizing potential risks, organizations need psychological support mechanisms integrated with technology. The Employee Assistance Program (EAP) is designed to help employees cope with psychological challenges that affect their work performance. With technological advancement, EAPs have evolved through the integration of artificial intelligence-based Employee Virtual Assistants (EVA), enabling real-time, personalized, and accessible psychological support. This approach offers a promising solution for balancing work engagement and psychological well-being in the workplace. This study employs a narrative review approach, developed as an extension of a previous systematic literature review (SLR) that explored the positive and negative impacts of work engagement. The review focuses on strategies to optimize engagement without compromising psychological well-being, emphasizing the roles of EAP and AI-based EVA. Relevant literature was sourced from Scopus, Google Scholar, ResearchGate, ScienceDirect, Springer, and SINTA, using inclusion criteria of English or Indonesian articles published in the last ten years (2014–2024). Findings indicate that integrating AI-based EVA within EAPs enables early detection of psychological distress, data-driven interventions, and improved access to mental health support, helping maintain sustainable and healthy work engagement. Keyword : Artificial intelligence (AI), Employee Assistance Program (EAP), Employee Virtual Assistant (EVA), Narrative Review, Psychological Well-Being (PWB), Work Engagement.